Application of Dynamic Systems to Model Increasing Profitability of UMKM Production in the “SENTRA IKAN BULAK” - Suyono, Joko; Rahmat, M. Basuki; Mudjanarko, Sri Wiwoho; Fadilah, Eka; Artaya, I Putu; Bahaswan, Rizal; Alie, R.M. Mahrus; Indartono, Arie; Syaiful, Syaiful; Alviansyah, M. Khakim; Umam, Choirul (LPPM of NAROTAMA UNIVERSITY, 2024)
The growth of UMKM in various sectors has triggered intense competition between these business actors. One of them is the craft sector. The use of social media is expected to boost turnover, but the benefits are still lacking. In the craft sector, the problem that arises on the MSME side is the cessation of production. This causes turnover to decrease and has an impact on decreasing profits. This dynamic system modeling is used to see how profit-increasing strategies can be carried out. Based on the dynamic system, there are several variables, namely the causal loop diagram (CLD) and the Stock Flow Diagram (SFD) that are built, there are 3 scenarios in increasing production profits, namely: increasing production, reducing the cost of tools and materials and the third is both taken simultaneously. From the simulation carried out, it was found that within a period of 12 months it was seen that increasing production by reducing the cost of tools and materials could increase sales so that income increased and profits increased. A process of identifying production process change variables is needed as one of the production process variables that was stopped.